Plasma testosterone and 11-ketotestosterone levels of male pacu Piaractus mesopotamicus (Cypriniformes, Characidae) - Gazola,R. (1997)
The levels of testosterone (T) and 11-ketotestosterone (11-KT) of the South American pacu Piaractus mesopotamicus were determined by radioimmunoassay during two stages of the reproductive cycle, i.e., resting and maturation, and the gonadosomatic index (GSI) was calculated. The highest levels of T and 11-KT were reached during the maturation stage (T = 2400 ± 56 pg/ml; 11-KT = 2300 ± 60 pg/ml) and lower levels were maintained during the resting period. The rise in androgen levels occurred with the appearance of spermatozoa in the maturation stage, when GSI was highest